2016
DOI: 10.1007/s13277-015-4629-y
|View full text |Cite
|
Sign up to set email alerts
|

Secretome profiling of oral squamous cell carcinoma-associated fibroblasts reveals organization and disassembly of extracellular matrix and collagen metabolic process signatures

Abstract: An important role has been attributed to cancerassociated fibroblasts (CAFs) in the tumorigenesis of oral squamous cell carcinoma (OSCC), the most common tumor of the oral cavity. Previous studies demonstrated that CAFsecreted molecules promote the proliferation and invasion of OSCC cells, inducing a more aggressive phenotype. In this study, we searched for differences in the secretome of CAFs and normal oral fibroblasts (NOF) using mass spectrometrybased proteomics and biological network analysis. Comparison … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0
6

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 63 publications
(52 citation statements)
references
References 54 publications
1
45
0
6
Order By: Relevance
“…The protumorigenic effects of CAF are related to the vast repertoire of secreted molecules, which can directly influence the behavior of cancer cells, stimulating proliferation, invasion, and metastasis. Some of the known molecules secreted by CAF include the stromal derived factor 1 (SDF‐1/CXCL12), activin A and matrix metalloproteases, some types of collagen and other extracellular matrix proteins such as fibronectin, and ROCK2 . Our findings in this study revealed ROCK2 positivity in both tumor and stroma cells, and a significant association between ROCK2 expression by tumor cells and the density of CAF was observed.…”
Section: Discussionsupporting
confidence: 52%
“…The protumorigenic effects of CAF are related to the vast repertoire of secreted molecules, which can directly influence the behavior of cancer cells, stimulating proliferation, invasion, and metastasis. Some of the known molecules secreted by CAF include the stromal derived factor 1 (SDF‐1/CXCL12), activin A and matrix metalloproteases, some types of collagen and other extracellular matrix proteins such as fibronectin, and ROCK2 . Our findings in this study revealed ROCK2 positivity in both tumor and stroma cells, and a significant association between ROCK2 expression by tumor cells and the density of CAF was observed.…”
Section: Discussionsupporting
confidence: 52%
“…In our sample, CCR4 was corre- and tumour microenvironment components. 14,15 Neoplastic cells are in permanent interaction with the microenvironment and cells of the connective tissue, such as cancer-associated fibroblasts (CAF) and immune cells. Furthermore, malignant cells are capable to modify the structure of its cytoskeleton and to express membrane receptors that facilitate its interaction.…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, treatment and prognosis of HNSCC are proposed according to the TNM stage, but nevertheless it has been observed that patients with the same TNM receiving similar therapeutic approaches have different evolution, evidencing that TNM is not always effective and new prognostic markers (adjuvants for TNM) are imperative in HNSCC. The aggressive features of HNSCC are dependent on the interactions between neoplastic cells and tumour microenvironment components . Neoplastic cells are in permanent interaction with the microenvironment and cells of the connective tissue, such as cancer‐associated fibroblasts (CAF) and immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…Carcinoma-associated fibroblasts (CAFs), which are identified by their intracellular α -SMA, are known predictors for poor prognosis in various malignancies (de Vlieghere et al , 2015), including OTSCC (Kellermann et al , 2007; Li et al , 2015; Bagordagis et al , 2016). However, CAFs are not prognostic indicators at early stage OTSCC (Almangush et al , 2014; Kelner et al , 2015), only in patient material of pooled stages, and at late stages when the variation in prognostic markers does not affect the choice of treatment so drastically, as more effective modalities are utilised in all cases.…”
Section: Resultsmentioning
confidence: 99%